Validation of a hybrid solar-electrical dryer through computational fluid dynamics simulation and practical approach applied to the Kent mango variety - Maximiliano Martín del Campo; Hector Huerta Avila; Elda Mireya Rodríguez González; Luz Orieta Rodríguez González (Smart Agricultural Technology)
This work addresses the overproduction of Kent mango in Jalisco, México, which often leads to significant post-harvest losses due to limited processing options. Drying is a viable preservation method, but traditional solar dryers rely solely on solar radiation, making them inefficient under variable weather conditions and continuous operation. This study evaluates a hybrid solar-electric dryer by comparing its performance in purely electric and combined solar-electric configurations using both Computational Fluid Dynamics simulations and experimental testing. Key challenges such as temperature control, energy efficiency, and drying uniformity are analyzed. Results show that the hybrid configuration reduces drying time by approximately 18% compared to the electric-only setup, reaching the target drying temperature (60°C) more rapidly and ensuring better temperature distribution. Experimental validation confirms these trends while highlighting additional real-world factors affecting drying performance. The novelty of this study lies in the integration of computer simulations with physical testing to optimize hybrid drying technology, providing a more efficient and scalable solution for mango dehydration.